EFEKTIFITAS PENERAPAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY DALAM UPAYA MEMBANGUN BRAND IMAGE PADA PT. TELKOMSEL KOTA BENGKULU - Fiona, Febzi; Susetyo, Sugeng; Nasution, Nasution; Widodo, Slamet; Puspita, Anggri (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aim to determine the implementation of CSR programs and measure the effectiveness of implementing CSR in building the brand image of PT. Telkomsel Bengkulu branch. Data collection methods used are the method of observation, interviews, and documentation. The results showed the implementation of the CSR program can improve communication and good relations between the company, the community, and its stakeholders. Besides, the implementation of CSR is considered useful in building the brand image. These implementations can be seen from the lack of conflicts that occur between companies, communities and increasing sales volumes. CSR implemented by PT. Telkomsel Bengkulu also consistently helps the company's sustainable growth. The results of this study can provide information for companies to implement CSR programs because it can sustainably help the company's sustainability. Keywords: CSR; Brand Image